The Perceptions of Medical Students Regarding Professionalism, a qualitative study - Kundi, Hina; Shauqat, Sadia; Waseem, Naureen; Imran, Shazia; Moazzam, Shazia; Yousaf, Maria (Journal of Rawalpindi Medical College, 2022)
Introduction: The elements of humanity and understanding the social values is significantly important for the health care workers to ensure positive health outcomes and patient’s safety, as care and empathy during the treatments are provided innately according to the standards, preferences and values of the individual. Aim: Our goal is to prepare finest quality physicians who will serve as role models for future medical practitioners. The aim of this study is to find out student’s perception regarding professionalism in order to design curricular contents and matching instructional strategies aiming at enhancement of professionalism, understanding, practice and behavioral change. Method: The study has been conducted at a private medical college in Islamabad after taking ethical approval. In order to collect data, a qualitative cross-sectional study design had been used. Focus group interview was conducted on semi structured questions. Data was recorded, transcribed, themes were extracted and analyzed by manual thematic analysis. Results: the study identified fundamental themes regarding professionalism. Students had fair knowledge regarding professionalism but lack deep understanding. It was suggested to practice role modelling in order to inculcate professionalism among medical students. Conclusion: The findings of the study indicated that the professionalism is the core of medical education and necessary for adequate practice therefore, we cannot rely on hidden curriculum for development of professional identity. The study suggests dire requirement for incorporation of study of professionalism and it applications in medical curriculum. Key words: Perceptions, Professionalism, Medical students